Quality of chicken breast meat improved by dietary pterostilbene referring to up-regulated antioxidant capacity and enhanced protein structure. (30th March 2023) - Wang, Yingjie; Zhou, Xin; Liu, Mengru; Zang, Haoran; Zhang, Ruoshi; Yang, Hao; Jin, Sanjun; Qi, Xueyan; Shan, Anshan; Feng, Xingjun
Highlights: Pterostilbene increased the sensory quality of chicken breast meat, especially WHC. Pterostilbene improved the quality of amino acids in chicken meat. Pterostilbene had positive effects on the MP structure of chicken meat. Pterostilbene enhanced the antioxidant capacity, reduced lipid and protein oxidation. Correlations between meat quality, MP structure and antioxidant status were explored. Abstract: This research aimed to investigate the effects of dietary pterostilbene supplementation on meat quality, myofibrillar protein (MP) structure and antioxidant capacity of broiler chicken. The results showed that pterostilbene increased pH24h, redness a *24h, water-holding capacity, and decreased yellowness b *24h and shear force of chicken meat; it also raised the crude protein, non-essential amino acid and flavor amino acid content in muscle. Pterostilbene increased Ca 2+ -ATPase activity and the α-helical ratio in muscle MP, accompanied by decreased dityrosine content and protein particle size, suggesting that pterostilbene addition effectively improved the MP structure. These alterations caused by dietary pterostilbene might be partially associated with the enhanced total superoxide dismutase, catalase and glutathione peroxidase activities regulated by genes relating to the Nrf2 signaling pathway, as well as reduced lipid and protein oxidation. Together, pterostilbene could be used as a promising dietary supplement for enhancing the organoleptic quality and nutritional value of chicken meat.